Wii-based interactive video games as a supplement to conventional therapy for rehabilitation of children with cerebral palsy: A pilot, randomized controlled trial. (18th August 2017) - Sajan, Jane Elizabeth; John, Judy Ann; Grace, Pearlin; Sabu, Sneha Sara; Tharion, George
ABSTRACT: Objective : To assess the effect of interactive video gaming (IVG) with Nintendo Wii (Wii) supplemented to conventional therapy in rehabilitation of children with cerebral palsy (CP). Design : Randomized, controlled, assessor-blinded study. Participants : Children with CP; 10 children each in the control and intervention groups. Intervention : IVG using Wii, given as a supplement to conventional therapy, for 45 min per day, 6 days a week for 3 weeks. The children in the control group received conventional therapy alone. Outcome Measures : Posture control and balance, upper limb function, visual-perceptual skills, and functional mobility. Results : Significant improvement in upper limb functions was seen in the intervention group but not in the control group. Improvements in balance, visual perception, and functional mobility were not significantly different between control and intervention groups. Conclusions : Wii-based IVG may be offered as an effective supplement to conventional therapy in the rehabilitation of children with CP.